Association of overweight and obesity with obstructive sleep apnoea: A systematic review and meta-analysis. (March 2020) - Dong, Zhiyong; Xu, Xiling; Wang, Cunchuan; Cartledge, Susie; Maddison, Ralph; Shariful Islam, Sheikh Mohammed
Abstract: Background: Research evidence suggests a close relationship between overweight and obesity with obstructive sleep apnoea (OSA); however, the extent of this relationship among different population groups is relatively unknown. The aim of this paper was to conduct a systematic review and meta-analysis to determine the magnitude of association of overweight and obesity with OSA in different population groups. Methods: We searched five electronic databases (Medline, Embase, Cochrane Library, CBM and CNKI) from inception to December 2017 for comparative epidemiological studies assessing the relation between overweight and obesity with OSA. Studies were included if they reported OSA by polysomnography and overweight/obesity by body mass index. Two authors independently screened titles and abstracts, selected studies and extracted data. Study quality was assessed using the Newcastle-Ottawa Scale. Random effects meta-analysis was used to estimate pooled effect sizes with 95% confidence intervals (CI). Heterogeneity was examined using Cochrane's Q statistic and I 2 test and explored using subgroup analyses for adults and children, adjusting for potential confounders. Publication bias was assessed using a funnel plot. Results: Twelve case-control studies encompassing a total of 3214 participants (Obese group n = 773, Non-Obese group n = 315; OSA group n = 1742, Non-OSA group n = 384) were analyzed. Results showed that increased body mass index was associated with higher risk of OSA in the adult group. The Obese group was associated with increased risk of apnoea-hypopnoea index (AHI) compared to the Non-Obese group and the differences were statistically significant in both children (Mean Difference = 12.29; 95% CI 8.46–16.11; P < 0.00001) and adults (Mean Difference = 12.11; 95% CI 4.35–19.85; P = 0.002). Conclusions: These findings suggest that overweight and obesity are important risk factors for OSA in both adults and children. Future studies are required to determine the effects of weight loss interventions in the development of obesity-related OSA. Highlights: This was the first study to examine the magnitude of association of overweight and obesity in different population groups. Obesity is significantly associated with increased risk of apnoea-hypopnea index (AHI). Overweight and obesity are important risk factors for OSA in both adults and children.